Competition in product design: an experiment exploring innovation behavior - Uwe Cantner; Werner Güth; Andreas Nicklisch; Torsten Weiland (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We experimentally investigate competition in innovation in a patent race scenario. Pairs of subjects compete as seller firms on a duopoly market, engaging in risky search investments. Successful innovation is rewarded through temporary monopoly rents. Throughout the interaction, subjects receive feedback on own and others search success and profit margin. Partitioning subjects into subgroups of investor types reveals that the majority of subjects condition investments on the degree of competition as measured by sales shares, while for others no correlation is ascertained. Heterogeneity in individual risk attitudes and differing experiences with related search tasks may explain this finding.
Keywords: D81; L11; O31; 330; innovation; competition; imitation; patent race; Innovation; Innovationswettbewerb; Imitationswettbewerb; Duopol; Produktdesign; Test